2015
DOI: 10.1186/s12906-015-0593-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro exposure to very low-level laser modifies expression level of extracellular matrix protein RNAs and mitochondria dynamics in mouse embryonic fibroblasts

Abstract: BackgroundLow-level lasers working at 633 or 670 nm and emitting extremely low power densities (Ultra Low Level Lasers - ULLL) exert an overall effect of photobiostimulation on cellular metabolism and energy balance. In previous studies, it was demonstrated that ULLL pulsed emission mode regulates neurite elongation in vitro and exerts protective action against oxidative stress.MethodsIn this study the action of ULLL supplied in both pulsed and continuous mode vs continuous LLL on fibroblast cultures (Mouse Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Additionally, PBM of complexes II and III still occurs with higher fluence lasers, despite previous concerns that the increased level of stimulation would be too strong 37. Though the focus has primarily been on enhanced effects of mitochondrial function, some have suggested that pulsed t-PBM may also increase the number of isolated mitochondria 38…”
Section: Proposed Mechanisms Of T-pbmmentioning
confidence: 99%
“…Additionally, PBM of complexes II and III still occurs with higher fluence lasers, despite previous concerns that the increased level of stimulation would be too strong 37. Though the focus has primarily been on enhanced effects of mitochondrial function, some have suggested that pulsed t-PBM may also increase the number of isolated mitochondria 38…”
Section: Proposed Mechanisms Of T-pbmmentioning
confidence: 99%
“…This subunit acts as a receptor for the laminin family. In a study conducted by Giuliani and colleagues [ 67 ] the daily irradiation of mouse embryonic fibroblasts for 3 days to a wavelength of 670 nm (pulsed wave, 0.21 mW/cm 2 , 4.3 mJ/cm 2 ) resulted in the up-regulation of ITGA5 . This is in contract to our study, but may be due to the different irradiation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, diabetic wounded fibroblast cells irradiated at the same parameters as in this study (660 nm; 5 J/cm 2 ) showed increased secretion of EGF, and subsequent activation of its receptor, EGFR [ 57 ]. Giuliani and colleagues [ 67 ] found no effect on the gene regulation of LAMA1 when they irradiated mouse embryonic fibroblasts (670 nm, 4.3 mJ/cm 2 ). They also found no effect on cadherin 1.…”
Section: Discussionmentioning
confidence: 99%
“…This test was performed by comparing Biolite emission with those of two lasers with the same wavelength and spot size but with different power/modulation (one at the same peak power but with no modulation and the other at 50 mW but with no modulation). Surprisingly enough, the Biolite effectiveness was significantly higher than the others (in press) [45]. (2) Effectiveness of Biolite emission in reinforcing the antibiotic treatment of Staphylococcus aureus [46].…”
Section: Biolite Developmentmentioning
confidence: 99%